Integrative and Complementary Practices as a mental health resource in Primary Health Care: Integrative Review (Research, Society and Development, 2022)
Objective: to compare among the types of Integrative and Complementary Practices (PICS) the benefits offered to users with mental disorders. Methodology: Integrative review carried out in Medline databases and in the Virtual Health Library (BVS), in English Composed of Clinical Trials published between 2018 and 2022, with primary data centered on the theme, involving adults and children, no sex restriction. Results and Discussion: 66 articles were computed, after applying the exclusion and inclusion criteria, 12 studies were listed to compose the final sample. The PICS that entered and were analyzed in the study were Acupuncture, Auriculotherapy, Yoga Meditation and Mindfulness. Through the analyzed studies, it was evidenced that the PICS addressed can be effective in patients with mental disorders in Primary Health Care (PHC). Final considerations: In summary, it is clear that the use of PICS in mental health improves among the types of disorders, the depressive, due to the use of opioids, and the Autistic Spectrum (ASD), as well as postpartum depression, cognitive impairment, memory and concentration disorders, alcohol withdrawal syndrome and smoking cessation.